Prognostic factors associated with postoperative adverse outcomes in patients with aortic valve prolapse. Issue 17 (April 2020) - Ruan, Yanping; Liu, Xiaowei; Meng, Xu; Zhang, Haibo; He, Yihua
Abstract: Background and aim: Aortic valve (AV) cusp prolapse and subsequent aortic insufficiency (AI) are 2 of factors leading to left ventricular (LV) enlargement and decreased LV function. Aortic valve replacement (AVR) has been the standard surgical procedure for AI. However, few data is available on the prognosis of these patients undergoing AVR procedure, especially in Chinese population. The study aims to evaluate the potential risk factors affecting the mid-term adverse outcomes after AVR. Methods: One hundred thirty-four patients (mean age: 46.7 years old) with AV cusp prolapse and severe AI who all received surgical aortic valve replacement were recruited in our hospital between January 1, 2009 and December 30, 2017. The clinical characteristics, echocardiography parameters, as well as operative parameters were obtained. The primary endpoint included death, heart failure development, and reoperation. Results: There were 14 adverse events altogether with the primary endpoint during a median follow-up of 8.6 (6–10) months. The multivariable Cox regression analysis revealed that baseline LVEDD (hazard rate, HR = 1.08, 95% CI: 1.01–1.15, P = .021), moderate pulmonary hypertension (HR = 9.36, 95% CI: 1.81–48.28, P = .008), and the time of assisted mechanical ventilation (HR = 1.01, 95% CI: 1.00–1.01, P = .022) were independently associated with the primary endpoint. Kaplan–Meier survival curve showed a significant worse survival free of the endpoint for patients with LVEDD≥70 mm, indexed LVEDD≥37.3 mm/m 2 (the mean in this study), indexed LVESD≥25 mm/m 2 or baseline LVEF <50% (all P <.05). Conclusion: Baseline enlarged LV dimensions, low LV function, moderate pulmonary hypertension, and prolonged assisted mechanical ventilation may predict the poor mid-term postoperative outcomes for AV cusp prolapse patients undergoing AVR procedure.